Diplomates en uniforme L'outil militaire dans la diplomatie française au Brésil (1956-1974) - Nabuco de Araujo, Rodrigo (Studia Remensia, 2022)
During the military dictatorship of 1968-1974, France sent its top intelligence specialists to Brazil. Coming from a variety of political backgrounds, these men ensured the transfer of the French army's colonial doctrines to the Brazilian army and created opportunities for the French industries that were reconstituted in the aftermath of the Second World War. In less than twenty years, the French army completely reshaped the Brazilian military's perception of its role. The technology exported was not just material, but also political. It enabled the construction of a new military system, based on the principle of anti-subversive warfare, the action of intelligence services and the hegemony of industrial groups linked to armaments. As a result, France made a significant contribution to the strategic autonomy of the Brazilian army, providing a significant alternative to the presence of the United States. Using a large number of archive documents, this book seeks to understand how these special links between the French and Brazilian militaries were built.